ROLE POSITION OF A MODERN TEACHER - Z.M. Miroshnyk (Academy of Cognitive and Natural Sciences, 2022)
The modern teacher's role position. In this article we discuss the professional training of teacher and focus your attention on an essential functions, which discharges the modern teacher. We accentuate teacher's position.